The Relationship Between Resilience and Religiosity in Medical Workers During the COVID-19 Pandemic - Nailah Nahdah, Rizqa; Natalia Stevani, Lastaida; Raulina Siahaan, Venessa (International Journal of Social Science, Education, Communication and Economics, 2024)
The COVID-19 pandemic posed unprecedented challenges to medical workers worldwide, compelling them to face intense workloads, psychological distress, and ethical dilemmas. This study examines the relationship between resilience and religiosity among medical workers during the pandemic. Resilience is understood as the capacity to adapt positively in the face of adversity, while religiosity refers to the degree of individual religious commitment and involvement. A mixed-methods approach was employed, combining quantitative data from validated surveys and qualitative insights from semi-structured interviews. The findings indicate a significant positive correlation between resilience and religiosity, suggesting that religiosity serves as a psychological buffer, enhancing resilience levels in medical workers. The study highlights the importance of integrating religiosity and resilience-building interventions into organizational policies to support medical workers during crises. The implications of these findings for future health policies and practices are discussed.